INVENTARISASI JENIS DAN RESEP KUE-KUE TRADISIONAL DI KOTA PADANG - Ginting, Yun Melita; Yulastri, Asmar; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The purpose of this study is to inventory kinds of traditional pastries, make traditional pastries inventory, knowing recipes traditional pastries and to describe functions that are of traditional pastries.The research is a qualitative . Data collection techniques Snow-Ball Sampling by observation, interview and documentation. Analysis of field data reduction, display, conclusion and verification. The results showed that 1) The type of traditional pastries of 2 types: patries and cakes moist 2) Inventory recipe recipe produces 44 traditional pastries in Padang 3) Recipe traditional patries, namely : there are 14 types of cake recipes tradisional dry and there are 30 kinds of cake recipes traditional wet 3)Function of pastries traditional in the city of Padang is as a snack, cake everyday, my custom, cake which was served on the day Eid and cakes made as a typical city of Padang.Keywords : Inventory, pastries tradisional, recipe, Padang city